Human Metapneumovirus in Focus: Emerging Insights into a Silent Respiratory Threat - Pokhriyal, Parshant; Anjum, Afsha; Kumari, Muskan; Naaz, Alisha (Indian Journal of Pharmacy Practice)
Human Metapneumovirus (HMPV) is a significant etiological agent of acute respiratory tract infections, with its most pronounced impact observed in the pediatric population. It also poses a substantial threat to elderly individuals and immunocompromised adults, often leading to severe complications. Despite being formally identified in 2001, serological evidence indicates the virus has been circulating in humans since at least the late 1950s, with its delayed discovery largely due to its fastidious growth requirements in cell culture. Human Metapneumovirus shares considerable genetic homology with avian metapneumovirus, suggesting a potential zoonotic origin, and is classified within the Metapneumovirus genus alongside Respiratory Syncytial Virus (RSV). The clinical manifestations of Human Metapneumovirus infection, which include bronchiolitis and pneumonia, closely mirror those of RSV, complicating differential diagnosis based on symptomatology alone. Confirmatory diagnosis relies on molecular methods such as PCR. At present, no targeted antiviral therapy exists; clinical management is primarily supportive, encompassing oxygen supplementation and fluid maintenance. Prevention centers on stringent hygiene measures and, for select high-risk groups, immunoprophylaxis. A comprehensive understanding of HMPV’s pathology, diagnostic approaches, and therapeutic limitations is vital for mitigating its public health burden, particularly among vulnerable groups.
Keywords: HMPV; Respiratory illness; Pneumovirus; Antibody